Rollover Prevention System for the Commercial Truck Based on Controlling the Steering Angle - (:unkn) unknown (My University, 2015)
0

Studies have shown that road accidents usually result in rollover. Therefore, the rollover dynamic is one of the most significant vehicle dynamic issues. The main objective of this study is to increase the safety margin of the commercial vehicle based on controlling the steering angle. The two-wheel vehicle model have been performed in order to obtain yaw rate and body lateral slip angle. Then, rollover model have been performed in order to obtain roll angle and roll rate of the vehicle during maneuvers. After Linear quadratic regulator and pole placement control system were used as the controller, uncontrolled system result was compared with the results of the two different controlled systems. The results indicate that pole placement controller gives better results than LQR in specific case
Keywords: Mühendislik, Makine